Diagnosis and management of shrimp allergy - Su, Bin Brenda; Blackmon, Warren; Xu, Chun; Holt, Christopher; Boateng, Nathaniel; Wang, Darren; Szafron, Vibha; Anagnostou, Aikaterini; Anvari, Sara; Davis, Carla M. (Frontiers in Allergy, 2024)
Shrimp allergy, the most common food allergy in the United States, affects up to 2% of the population. Its etiology is multi-factorial with the combination of genetic predisposition and environmental exposures. This review summarizes the latest diagnosis and management strategies for shrimp allergy. Currently, the double-blind, placebo-controlled food challenge is the gold standard for diagnosis. Moreover, mainstream and experimental management strategies include food allergen avoidance, the FDA-approved omalizumab, and oral immunotherapy. Herein, we emphasize the urgent need to develop more effective diagnostic tools and therapies for shrimp allergy.